Experimental and Numerical Analysis of Eccentrically Loaded Beam-Columns - Vican, Josef; Janik, Peter; Nikolic, Ruzica (Communications - Scientific letters of the University of Zilina, 2014)
The beam-column subjected to the combination of the axial force and the bending moments is an example of the very complicated task from the viewpoint of the design resistance verification. The general theoretical solution of the resistance assessment of that beam-column is not suitable for practical use due to complicated and non-general form. Then, the standard simplified approach is used. Therefore, the paper deals with the experimental and numerical analyses of the resistances of eccentrically loaded beam-columns and their comparison with the standard approaches. Discussion of results and conclusions related to further research direction are also presented in this paper.